The Screening of Fungi for Antagonistic Acidofilic Lignocellulolitic on Peat Soil of Fusarium Disease - Nursadin Nursadin; Iman Suswanto; Supriyanto Supriyanto (Fakultas Pertanian Universitas Tanjungpura, 2012)
Fusarium wilt disease is one of disease that considerable losses to the tomato plant. This disease can cause sudden death, this is due to damage to the base of the stem or cancer. Plants infected adults are able to survive and shape but the result is very little fruit and small fruit. Besides caused by pathogens, constraints cultivation in peatsoil is a peat substrate forming the lignin and cellulose are normally difficult to decompose. This study aims to find the best fungi as biological control agents against F. oxysporum and the ability to survive in acidic conditions and was able to decipher the compound lignin and cellulose. The research was conducted at the Laboratory of Plant Diseases Faculty of Agriculture, University of Tanjungpura Pontianak, January to June 2012. Implementation of the study include the isolation of fungi from peat soils, test antagonism towards the development of F. oxysporum, hipovirulensi test, capabilities and outlines the lignin and cellulose asidofilik test. Results isolation from peat obtained 7 isolates of fungi, that is Aspegillus brevipes, A. niger, Penicillium corylophillum, P. janthillenum, Rhizopus sp, Trichoderma harzianum and T. koningii. The test results antagonistic to F. oxysporum isolates obtained 2 are able to act as antagonists and suppressed the development of F. oxysporum. Both of these isolates were T. harzianum and T. koningii. Besides being able to act as antagonists, both isolates are able to decompose lignin into simpler compounds. In describing cellulose, A. niger has a greater ability than other isolates. Almost all isolates were classified into asidofilik fungus, only A. brevipes were not included asidofilik because diameter growth at pH 3 did not reach 75% compared to pH 6. Keywords: Antagonistic fungi, acidofilic, fusarium wilt.